Short-term artificial adaptation of Rhizoglomus irregulare to high phosphate levels and its implications for fungal-plant interactions: phenotypic and transcriptomic insights - Lucic-Mercy, Eva; Mercy, Louis; Jeschke, Andrea; Schneider, Carolin; Franken, Philipp (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) play a crucial role in enhancing plant growth, but their use in agriculture is limited due to several constraints. Elevated soil phosphate levels resulting from fertilization practices strongly inhibit fungal development and reduce mycorrhizal growth response. Here, we investigated the possibility of adapting Rhizoglomus irregulare to high phosphate (Pi) levels to improve its tolerance. A fungal inoculum was produced through multiple generations in the presence of elevated Pi and used to inoculate melon plants grown under low and high phosphate conditions. Our results revealed distinct phenotypic and transcriptomic profiles between the adapted and non-adapted Rhizoglomus irregulare. The Pi adapted phenotype led to enhanced root colonization under high Pi conditions, increased vesicle abundance, and higher plant biomass at both phosphate levels. Additionally, the adaptation status influenced the expression of several genes involved in Pi uptake, Pi signaling, and mitochondrial respiration in both symbiotic partners. While the underlying mechanisms of the adaptation process require further investigation, our study raises intriguing questions. Do naturally occurring phosphate-tolerant AMF already exist? How might the production and use of artificially produced inocula bias our understanding? Our findings shed light on the adaptive capacities of Glomeromycota and challenge previous models suggesting that plants control mycorrhizal fungal growth. Moreover, our work pave the way for the development of innovative biotechnological tools to enhance the efficacy of mycorrhizal inoculum products under practical conditions with high phosphate fertilization.